Analisis Teks dan Konteks Pada Kolom Opini Kompas Mewaspadai Ledakan Mudik 2024 - Putri, Valencia Eka Armanda; Iskandar, Dinda Sabrina; Salsabila, Anindya Putri (STKIP PGRI Ponorogo Press, 2024)
Basically, the role of language in communication, whether verbal or written, is very important. Basically, the interaction process can run smoothly if the communicator and the interlocutor understand the context, both the situational context and the sociocultural context of the topic being discussed. The main aim of this analysis is to describe the context and text of the opinion article